2004
DOI: 10.2337/diacare.27.8.1873
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Diabetic Ketoacidosis With Subcutaneous Insulin Aspart

Abstract: OBJECTIVE—In this prospective, randomized, open trial, we compared the efficacy and safety of aspart insulin given subcutaneously at different time intervals to a standard low-dose intravenous (IV) infusion protocol of regular insulin in patients with uncomplicated diabetic ketoacidosis (DKA). RESEARCH DESIGN AND METHODS—A total of 45 consecutive patients admitted with DKA were randomly assigned to receive subcutaneous (SC) aspart insulin every hour (SC-1h, n = 15) or every 2 h (SC-2h, n = 15) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
144
5
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(160 citation statements)
references
References 35 publications
(44 reference statements)
2
144
5
9
Order By: Relevance
“…Two studies analyzing the use of subcutaneous insulin for DKA on medicine wards found rates of hypoglycemia closer to 5% but used a lower threshold for hypoglycemia (< 60 mg/dl). 9,10 The incidence of hypoglycemia after conversion to subcutaneous insulin was slightly higher than what was found in a study by Umpierrez et al, 11 which documented a range of 15-41% depending on the type of insulin to which patients were converted.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Two studies analyzing the use of subcutaneous insulin for DKA on medicine wards found rates of hypoglycemia closer to 5% but used a lower threshold for hypoglycemia (< 60 mg/dl). 9,10 The incidence of hypoglycemia after conversion to subcutaneous insulin was slightly higher than what was found in a study by Umpierrez et al, 11 which documented a range of 15-41% depending on the type of insulin to which patients were converted.…”
Section: Discussioncontrasting
confidence: 48%
“…Previous studies have shown that patients with DKA can be safely and effectively treated with subcutaneous insulin on medicine wards; however, we have not identified any studies of ward treatment of DKA with continuous infusions of insulin. [8][9][10][11][12] The Medical University of South Carolina (MUSC) treats a similar percentage of patients on general medicine wards, as seen in the New York study described above, 7 using an internally developed, Internetbased, nursing-driven insulin infusion protocol. The safety and efficacy of the MUSC protocol was validated in a population of cardiothoracic surgery patients.…”
mentioning
confidence: 99%
“…[162,163]. There were no differences in length of hospital stay, total amount of insulin needed for resolution of hyperglycemia or ketoacidosis.…”
Section: Insulin Therapymentioning
confidence: 83%
“…There were no differences in length of hospital stay, total amount of insulin needed for resolution of hyperglycemia or ketoacidosis. Patients treated with insulin analogs were managed in the open medical wards which reduced cost of hospitalization by 30% [162][163][164]. This approach is not widely used for many reasons, including titration difficulties with longer half-life preparations, requirement for hourly nursing interventions and lack of staff experience compared to that with standard insulin infusions.…”
Section: Insulin Therapymentioning
confidence: 99%
See 1 more Smart Citation